(untitled) (Journal of Global Humanities and Social Sciences, 2026)
In the digital era, immersive technologies—including Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR)—are profoundly reshaping the preservation and dissemination of cultural heritage. Focusing on digital authenticity and cultural dignity, this paper explores the theoretical foundations, practical risks, and legal governance mechanisms of immersive cultural heritage reconstruction. While immersive technologies enhance public engagement and cultural accessibility, they also risk distorting historical contexts and cultural meanings, leading to the erosion of digital authenticity and the violation of cultural dignity. By analyzing the limitations of China’s Cultural Relics Protection Law, Copyright Law, and Civil Code, the study proposes a multidimensional governance framework guided by the principles of “Respect First, Public Interest Orientation, and Collaborative Governance.” This framework integrates legal enhancement through digital-specific provisions, ethical regulation via participatory guidelines, and technical safeguards through metadata and traceability standards. The research aims to shift the paradigm of cultural heritage protection from a technology-centered to a culture-centered model, contributing to the interdisciplinary integration of digital humanities and legal governance.